TYPOLOGY OF RISKS IN RFID: TYPOLOGY OF RISKS IN RFID - Kazakov, Stefan; Jordanova, Jordanka (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Radio Frequency Identification (RFID) is still evolving technology. It is technology with many possible applications. There are also many different possible frequencies, different physical forms of RFID tags, different possible use cases for RFID readers. There are also many standards related to RFID. In this paper state of RFID standards is presented. Typology of RFID systems according to six different criteria was proposed. This overview can serve for engineers, managers and decision makers, when doing first insights into technology.